2007
DOI: 10.1080/00224490709336794
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the “Wantedness” of Women's Consensual and Nonconsensual Sexual Experiences: Implications for How Women Label Their Experiences With Rape

Abstract: Sex is often conceptualized either as wanted and consensual or as unwanted and nonconsensual, reflecting an implicit model of wanting that is unidimensional and dichotomous and that conflates wanting and consenting. This study had three objectives: developing a multidimensional model for conceptualizing the wantedness of a sexual act, using this model to compare women's experiences with rape and consensual sex, and assessing whether wantedness is related to rape acknowledgement. Participants were college women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
192
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(202 citation statements)
references
References 28 publications
9
192
1
Order By: Relevance
“…As noted by Peterson and Muehlenhard (2007) Procedures Procedures for the current study involved college students, ranging in major and age, enrolled in an introductory communication course completing an online survey. Specifically, students enrolled in the introductory communication class were asked to participate in one of the studies posted in the course subject pool and that they would receive credit for participation.…”
Section: Methods Scenariosmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted by Peterson and Muehlenhard (2007) Procedures Procedures for the current study involved college students, ranging in major and age, enrolled in an introductory communication course completing an online survey. Specifically, students enrolled in the introductory communication class were asked to participate in one of the studies posted in the course subject pool and that they would receive credit for participation.…”
Section: Methods Scenariosmentioning
confidence: 99%
“…The authors indicate that nonconsensual sex, even if wanted by the target, is still rape. Further, the distinctions advanced in their multidimensional model are important as they also contribute to survivors' perceptions of the situation, reportability of the event, and recovery from it (Botta and Pingree 1997;Peterson and Muehlenhard 2007). Individuals' perceptions of the aforementioned contexts might vary, however.…”
Section: Sexual Aggressionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rape myths and rape scripts can narrow victims' definitions of rape and decrease the likelihood that victims will acknowledge an event is rape (Peterson and Muehlenhard 2004). In addition, the presence of an experience that strongly contradicts the real rape script (e.g., a victim's initial sexual desire) may prevent the application of the rape label to nonconsensual sexual experiences (Peterson and Muehlenhard 2007). It is also possible that victims might resist labeling their experience as rape because of the perceived negative ramifications of being a rape victim, including changes in worldview and view of self (Crome and McCabe 2001).…”
Section: Rape Scripts and Sexual Predationmentioning
confidence: 97%
“…In a study of young women, Peterson and Muehlenhard (2007) found that women experienced sexual "wantedness" as a multidimensional and continuous construct. That is, women reported wanting and not wanting sex to various degrees and for various reasons.…”
Section: Is Sexual Empowerment All-or-none?mentioning
confidence: 98%